Cultures of colour : visual, material, textual - Horrocks, Chris (Berghahn Books, 2012)
Colour permeates contemporary visual and material culture and affects our senses beyond the superficial encounter by infiltrating our perceptions and memories and becoming deeply rooted in thought processes that categorise and divide along culturally constructed lines. Colour exists as a cultural as well as psycho-physical phenomenon and acquires a multitude of meanings within differing historical and cultural contexts. The contributors examine how colour becomes imbued with specific symbolic and material meanings that tint our constructions of race, gender, ideal bodies, the relationship of t.